Shared Habitats: A Cultural Inquiry into Living Spaces and Their Inhabitants - Gapsevicius, Mindaugas; Damm, Ursula (transcript, 2021)
The interactions between artistic, technical, scientific, living, and nonliving things have inspired new artistic approaches. The contributors to this volume either relate to theoretical discourses raised by artworks, show how young artists today approach cultural issues, or develop situations of living together with other species. All the contributions to this publication by writers, artists, technologies, and other organisms invite the reader into new experiences and new imaginaries. The reader is also invited to rethink the role of art and the role of the artist within umwelts, milieus, and habitats.